Human Trafficking As A Serious Human Rights Violation In The Digital Era: An Islamic Law Approach - A.Ameisabila; A. Mutma’inna; Susianti, Susianti; A. Mattoriang; Hamzah, Hamzah (proceedings.icesy, 2026)
Human trafficking is a form of serious human rights violation that has become increasingly complex along with the development of the digital era. This study is a library research with a normative juridical approach. Data were collected through literature studies such as books, journals, the Qur’an, Hadith, and legislation related to human trafficking. The results of the study show that human trafficking in the digital era is an increasingly complex crime because it utilizes the development of information and communication technology. Human trafficking meets the criteria of a serious human rights violation because it contradicts the principles of human rights protection guaranteed by legislation. From the perspective of Islamic law, human trafficking is considered a forbidden act and is classified as a serious crime. The Qur’an and Hadith explicitly prohibit all forms of slavery, coercion, and human exploitation based on the principle of human dignity (karāmat al-insān). The implication of this study enhances the understanding that human trafficking in the digital era is a serious crime categorized as a severe human rights violation and requires comprehensive handling.